The social cost of cheap food : labour and the political economy of food distribution in Britain, 1830-1914 - Rioux, Sébastien, 1980- (McGill-Queen's University Press, 2019)
"The distribution of food played a considerable yet largely unrecognized role in the economic history of Victorian and Edwardian Britain. In the midst of rapid urbanization and industrialization, retail competition intensified and the channels by which food made it to the market became vital to the country's economic success. Illustrating the pivotal importance of food distribution in Britain between 1830 and 1914, The Social Cost of Cheap Food argues that labour exploitation in the distribution system was the key to cheap food. Through an analysis of labour dynamics and institutional changes in the distributive sector, Sébastien Rioux demonstrates that economic development and the rising living standards of the working class were premised upon the growing insecurity and chronic poverty of street sellers, shop assistants, and small shopkeepers. Rioux reveals that food distribution, far from being a passive sphere of economic activity, provided a dynamic space for the reduction of food prices. Positing food distribution as a core element of social and economic development under capitalism, The Social Cost of Cheap Food reflects on the transformation of the labour market and its intricate connection to the history of food and society."--